It is time to talk about people: a human-centered healthcare system - Borgi Lea; Searl Meghan M; Chemali Zeina (BMC, 2010)
Abstract Examining vulnerabilities within our current healthcare system we propose borrowing two tools from the fields of engineering and design: a) Reason's system approach <abbrgrp>1</abbrgrp> and b) User-centered design <abbrgrp>23</abbrgrp>. Both approaches are human-centered in that they consider common patterns of human behavior when analyzing systems to identify problems and generate solutions. This paper examines these two human-centered approaches in the context of healthcare. We argue that maintaining a human-centered orientation in clinical care, research, training, and governance is critical to the evolution of an effective and sustainable healthcare system.